A regularity criterion for 3D shear thinning fluids in terms of the direction of vorticity. (April 2023) - Sin, Cholmin
Abstract: We prove that a weak solution for unsteady 3D shear thinning flows is strong under the certain assumption about the direction of the vorticity for 5 3 < p ≤ 2 . As an auxiliary result, we show the short time existence of strong solution for whole space.